Characterization and photocatalytic activity of nanoparticulate PrVO4 prepared by hydrothermal method. (18th August 2019) - Sun, Liangyun; Tang, Peisong; Ding, Yangbin; Lin, Xihao; Chen, Haifeng
Abstract: Using praseodymium nitrate (III) hexahydrate (Pr(NO3 )3 ·6H2 O), ammonium metavanadate (NH4 VO3 ) and hexadecyl trimethyl ammonium bromide (CTAB) as raw materials, PrVO4 samples were successfully prepared by hydrothermal method. The resulting samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), thermogravimetric and differential scanning calorimetry (TG-DSC), UV–visible diffuse reflectance spectroscopy (DRS) and Fourier transform infrared spectroscopy (FT-IR). The effect of different synthesis temperature and illumination time on the ultraviolet photocatalytic activity of PrVO4 samples was studied with methyl orange solution as simulated sewage. The results show that the pure tetrahedral zircon structure of the PrVO4 sample can be obtained at a hydrothermal temperature of 100–180 °C. The sample of PrVO4 prepared by hydrothermal temperature at 140 °C was uniform, with an average particle diameter of 50–60 nm and a band gap width of 3.1 eV. The photocatalytic experiment demonstrates that the degradation rate of 100 mg/L methyl orange is nearly 92.4% in the presence of PrVO4 sample prepared at 140 °C after UV irradiation at 30 min. The PrVO4 samples show excellent photocatalytic performance for degradation of methyl orange.